The Paradox of Awards: How Status Ripples Affect Who Benefits from CEO Awards - Jensen, Michael; Twardawski, Torsten; Younes, Nadja (Organization Science, 2022)
Distinguishing between status spillovers and status ripples, we argue that sudden positive status shifts create status ripples when the social actors experiencing the status shifts are more constrained from exploiting their higher status than the social actors to whom they are affiliated. Specifically, we examine the status ripple paradox that the status effects experienced by the affiliated actors sometimes are as strong, or even stronger, as the direct status effects experienced by the ascending actors themselves. Focusing empirically on prestigious CEO awards from U.S. news magazines, we examine the consequences of positive status shifts for the awarded CEOs and the CEOs who are on the boards of directors of the awarded CEOs’ firms. We find evidence of status ripples in CEO compensation by showing that awarded CEOs have relatively greater immediate but smaller subsequent increases in compensation, which results in lower overall compensation effects for the awarded CEOs. Moreover, we provide empirical evidence of the theoretical mechanisms behind the status ripple paradox by showing that external constraints in the form of increased media and analyst attention and increased expectations affect the status ripple effect.